Assessment of Surface Water Quality of Noyyal River Using Wasp Model - Mahalakshmi, G.; Kumar, M.; Ramasamy, T. (Asian Journal of Engineering and Applied Technology, 2018)
The Noyyal River is a tributary of river Cauvery has been one of the most predominant and important rivers of Tamil Nadu. Unfortunately, certain stretches of river Noyyal are polluted due to effluent discharge from the industries and domestic sewage. The effective water environmental management strategies required to be implemented in this river to upgrade the water quality and to ensure sustainable development in the region. The aim of this work was to provide a basis for water environmental management in process of making important decisions. In this study WASP (Water Quality Simulation Program) is used as a model to identify the processes that underlie river water quality problems in a basin. WASP was recommended by EPA used as water quality model. Simulated values of Nitrate (NO3), Dissolved Oxygen (DO), Total Dissolved Solids (TDS), Alkalinity and pH demonstrated the accuracy of the model and despite a significant data shortage in the study area. WASP model was found to be an acceptable tool for the assessment of water quality.